Analyzing the droughts and their determinants in the Fuhe River Basin using the SWAT model - LIU Mingchao; JIAN Hongfu; HAN Huiming; LONG Peng (Guan'gai paishui xuebao)
【Objective】 The Fuhe River Basin is an important food production region in Northwestern China. It is increasingly affected by droughts. This paper analyses the occurrence of droughts and their key determinants in this region. 【Method】 The analysis was based on modelling. We simulated the changes in monthly soil water content from 1962 to 2019 using the SWAT model. The resulting data were then used to calculate the standardized soil moisture index. The characteristics of agricultural droughts were analyzed using the theory of runs, and the key determinants of the droughts were analyzed using the geographical detector. 【Result】 ① The coefficient of determination (R2) and the Nash efficiency coefficient (ENS) between the modelled and measured results in the calibration are both higher than 0.80; the coefficient of determination between the predicted soil moisture content and the measured soil moisture content is 0.52. ② The duration of droughts in different regions in the basin varied from 3.60 to 4.31 months, and the drought intensity ranged from 4.91 to 5.61, both varying spatially, higher in the North and South and lower in the center. ③ The influence of temperature, solar radiation, and wind speed on spatial variation in the droughts, characterized by the q-value, exceeds 0.30. Other environmental factors are nonlinearly interacted in their influence on the droughts. 【Conclusion】 The standardized soil moisture index can quantitatively characterize droughts in the Fuhe River Basin. Droughts in the basin vary spatially, with temperature, solar radiation and wind speed being the main contributing factors.